The light-independent locomotion response to a static magnetic field in Xenopus tadpoles - Ren, Jie; Mo, Weichuan; Zhang, Haitao; He, Rongqiao; Wang, Xiumei; Jiang, Tao; Liu, Ying (Frontiers in Physics, 2022)
Increasing numbers of behavioral observations have shown that many organisms can sense magnetic fields in the environment. However, the underlying mechanisms of magnetosensation remain elusive, and a major problem is the lack of an animal model convenient for detecting magnetic responses, especially in vertebrates. We have previously reported that the physical performance of mice decreased after one month of exposure to a hypomagnetic field, which probably includes a light-independent mechanism. In this study, we investigated the effects of a static magnetic field on the locomotion of Xenopus tadpoles (stage 48) using a real-time recording system. Because it is speculated that the photosensing system is related to magnetosensation, we triggered the tadpoles to swim by a 30 s light pulse after a 5 min adaptation in the dark and measured the swimming activities of the tadpoles under static magnetic field exposure in both the dark and bright conditions. Compared to the sham control treatment, the presence of a magnet inhibited the movement of the tadpoles under both bright and dark conditions, as shown by reductions in swimming distance, speed, and counts of path adjustment. Moreover, the directional preference for path adaptation was altered when swimming in the dark. These results suggest that tadpoles in the dark can exert a rapid locomotion response to changes in the environmental magnetic field, providing evidence for an intrinsic, light-independent rapid magnetoresponse and pathway in tadpoles. In addition, this rapid vertebrate locomotion assay paradigm will be a practical tool to facilitate further investigation of the mechanisms of bio-magnetic effects.